2012
DOI: 10.1103/physreva.86.062309
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the tradeoff between fidelity and time optimal control of quantum unitary transformations

Abstract: Generating a unitary transformation in the shortest possible time is of practical importance to quantum information processing because it helps to reduce decoherence effects and improve robustness to additive control field noise. Many analytical and numerical studies have identified the minimum time necessary to implement a variety of quantum gates on coupled-spin qubit systems. This work focuses on exploring the Pareto front that quantifies the trade-off between the competitive objectives of maximizing the ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
105
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 73 publications
2
105
2
Order By: Relevance
“…Quantum optimal control theory (OCT) provides a basis to explore applied field tuning of quantum system dynamics [1,2,3,4,5]. Recent successes include achieving control of electrons in quantum dots through time-varying gate voltages [6], controlling electronic correlations in molecules [7], manipulating the dynamics of quantum many-body systems [8], cooling ultracold atomic gases [9], eliciting quantum revivals [10], and generating adiabatic time evolution [11].…”
Section: Introductionmentioning
confidence: 99%
“…Quantum optimal control theory (OCT) provides a basis to explore applied field tuning of quantum system dynamics [1,2,3,4,5]. Recent successes include achieving control of electrons in quantum dots through time-varying gate voltages [6], controlling electronic correlations in molecules [7], manipulating the dynamics of quantum many-body systems [8], cooling ultracold atomic gases [9], eliciting quantum revivals [10], and generating adiabatic time evolution [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several OCT studies have shown that violating condition (3) by limiting the number of control variables [180] or the control period T [81,168,[170][171][172][173][174][175][176][177][178][179] can prevent the achievement of a globally optimal solution. In this section, we investigate the practical effects of imposing various types of constraints.…”
Section: Effects Of Severe Control Field Constraintsmentioning
confidence: 99%
“…In this paper, we focus on the subset of severe constraints, i.e., those that prevent achievement of the target objective by introducing local optima onto the control landscape. It has been shown, however, that even more mild constraints can have a significant effect on OCT optimizations, e.g., by increasing the search effort [163][164][165][166][167][168].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1d were implemented with a control time and phase step duration identified as nearoptimal based on computer-numerical and laboratory exploration [29]. Figure 2 shows the average fidelity calculated for that set of maps when implemented with waveforms using a range of (T, δt).…”
mentioning
confidence: 99%